Tobacco Smuggling and the French Consulate in Galicia in the 1730s - García Hurtado, Manuel-Reyes (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The French consulate in Galicia had to defend the commercial interests of the Crown in a territory where the activity of smuggling, especially of tobacco, was closely monitored. In the context of a transformation of the tobacco revenue administration system in 1730, there was an intensification in the fight against the illegal trade, which the documentation shows was supported by the consular body. This is an example of the determined defense of what are considered to be the privileges and exemptions that French ships must enjoy in Spanish ports; it does not obey their economic relevance to France. The rejection of the inspection of vessels, the placement of guards on board, and the obligation to anchor, are elementsthat contribute to facilitating smuggling.